Association of cardiac autonomic nerve function with serum zinc, calcium and magnesium in female hypothyroid patients - Mannan, Mahua; Sultana, Shamima; Sarkar, Bipasha; Sarkar, Nandita (Journal of Bangladesh Society of Physiologist, 2024)
Background: Hypothyroidism is related to impaired cardiac autonomic nerve activity with altered levels of serum Zinc (Zn), Calcium (Ca) ‍and Magnesium (Mg).Altered Serum Zn,Caand Mg levels are also associated with autonomic imbalance and may raise cardiovascular risk.Heart rate variability (HRV) is an important marker for assessing cardiac autonomic nerve function(CANF). Objectives: To evaluate the association of serum Zn, Cal and Mglevels withCANF in female hypothyroid patients. Methods: This analytical cross-sectional study was conducted on 40 female hypothyroid patients aged 18-45 years. Thirty apparently healthy women were control. Serum Zn, Ca and Mg levels were estimated by autoanalyzer and CANF was assessed by time domain analysis of HRV recorded by Power Lab 8/35 AD Instruments, Australia. Statistical analysis was done by Independent sample‘t’ test, One way ANOVA followed by post-hoc Bonferroni test and Pearson’s correlation coefficient test. Results: Among time domain parameters of HRV, standard deviation of the RR intervals (SDRR), coefficient variation of RR interval (CVRR), SD rate, standard deviation of the difference between successive RR intervals (SDSD), square root of mean squared differences of successive RR intervals (RMSSD), proportion of RR interval with duration >50 ms (pRR50%) were significantly lower (p<0.05) in all hypothyroid patients as compared to control. On correlation analysis, serum Zn, Ca and Mg were significantly positively correlated with SDSD(p<0.01, p<0.001,p<0.01) RMSSD(p<0.01, p<0.001, p<0.01), pRR50%(p<0.01, p<0.01, p<0.05)and serum Ca was also positively correlated with SDRR(p<0.05) in hypothyroid patients. Conclusion:Serum ZnCa and Mg were associated with cardiac autonomic dysfunction. in female hypothyroid patients. J Bangladesh Soc Physiol 2023;18(1): 27-34